Accountability and the postcolonial identity of Palestinian human rights NGO activists - Alshurafa, Mohammed; Kamla, Rania (Accounting, Organizations and Society, 2024)
We incorporate conceptualisations around the accountable self into the NGO accountability literature to consider how NGO human rights activists make sense of their accountability in relation to their postcolonial identity. We conducted 21 semi-structured interviews with Palestinian activists working in Palestinian and Israeli NGOs defending human rights in Gaza. Our findings provide four original insights. First, the construction of their identity as “postcolonial” considerably motivates our interviewees' work as human rights activists, but also creates conflicts with NGOs' humanitarian missions. Activists respond by stressing their postcolonial identity over their professional one. Second, due to Palestinian activists' own lived experiences, they construct accountability relations and collective identities defined by victimhood. The sense of victimhood results in blurring boundaries between activists and their “beneficiaries”, which influences their sense of accountability and motivates their practices. Third, the accountable self mobilises different accountability practices to deal with both the self's needs for narrativity and authenticity (e.g., through storytelling and remembrance) and external demands for “objective” accounts, thereby balancing their postcolonial and professional identities and responsibilities. Fourth, our interviewees sense that their accountability has limitations, as the accounts of human rights violations they produce receive insufficient recognition from others. Overall, the study indicates the importance of considering how a postcolonial identity of human rights activists creates various sources and motivations for the accountable self's relationships, practices and limitations distinguishable from, but linked, to those practised by NGOs.